Determinanty i założenia polityki proeksportowej w początkowym okresie transformacji gospodarki polskiej - Domiter, Małgorzata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Polish commerce policy cannot be considered without economic and political context. It is a part of macroeconomic policy. We can distinguish between external and internal determinants of commerce policy. Among external determinants of Polish commerce policy very important are liberal and global conceptions of GATT/WTO and the EU. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1147, s. 113-125